Restorative Justice as a Means to Achieve Justice and Legal Certainty in Defamation Cases - Arma Sentia Putri, Renalda; Gary Gagarin Akbar, Muhamad; Abas, Muhamad (Faculty of Law, University of Mataram, 2024)
Restorative justice is an alternative approach to resolving legal conflicts, including defamation cases, which emphasizes peaceful settlement outside the court. This process involves cooperation among the perpetrator, victim, families, and the community to find a fair solution. This research highlights the importance of implementing restorative justice in handling defamation cases, which often cause psychological harm to victims, especially in the digital era where the internet and information technology facilitate the unlimited dissemination of information. Currently, the enforcement of laws, particularly regarding defamation offenses, is frequently criticized for failing to provide full justice, especially when imprisonment is imposed. Authorities often use articles related to defamation and insults in the Indonesian Criminal Code (KUHP), such as Articles 310 and 311, along with Law No. 11 of 2008 on Electronic Information and Transactions (ITE), as the basis for legal action. However, this approach neglects the aspects of recovery for victims and rehabilitation for offenders. This study aims to understand how restorative justice can be applied to defamation cases via social media, focusing on mediation aimed at achieving peace among the involved parties. The methodology employed is normative juridical research, with an analysis of relevant legislation. The findings indicate that a restorative approach can offer a fairer and more humane solution to defamation, particularly in the digital era. The implications of this research highlight the need to integrate restorative justice within the criminal justice framework, especially regarding cybercrimes.